Giant calyceal diverticulum in a child with solitary kidney: A rare experience - Anindya Chattopadhyay (Wolters Kluwer Medknow Publications, 2021)
Calyceal diverticuli are rare entities which are difficult to diagnose radiologically as they mimic various other pathology.Close follow up is essential even in asymptomatic individuals to prevent complications. The authors present a giant calyceal diverticulum in a solitary kidney in a child that was managed by open surgery.